Teachers’ perceptions and attitudes on the use of tablet computers in teaching and learning process: Experiences from face-to-face sessions at Morogoro-campus in Tanzania - Magembe, Kija Steven (International Journal of Educational Technology and Learning, 2025)
This study assessed teachers’ perceptions and attitudes regarding integrating tablet computers into the teaching and learning process. A mixed-methods approach and a descriptive design were employed. The Technology Acceptance Model (TAM) was used to assess teachers’ perceived usefulness, ease of use, behavioral intention to use, attitudes toward tablet computers, and challenges associated with the use of tablet computers in the learning and teaching process. Sixty-four (64) respondents participated in the study and were selected through purposive sampling during a face-to-face session held in December 2023 at Morogoro-Campus. Data in this study were collected using questionnaires and interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data underwent thematic analysis. The findings revealed that teachers generally perceived tablets as effective teaching tools and expressed satisfaction with their use in the teaching and learning process. However, the study highlighted a lack of training for teachers on incorporating tablet computers into classroom. Key barriers included insufficient technical support, connectivity issues, and time constraints. 76.6% (f = 49) of the respondents believed that providing clear and appropriate information on how, when, and where to use tablets would enhance their effectiveness in teaching. Respondents also emphasized the importance of training teachers in the use of tablet computers to ensure that they are equipped with the necessary skills to integrate technology effectively into their teaching practices. The study recommends providing in-service training for teachers on utilizing tablet computers in education.